Chemical Analysis and Biological Activities of Essential Oils from Trunk-Barks of Eight Trees - KOLAYLI, SEVGI; OCAK, MIRAC; ALIYAZICIOGLU, REZZAN; KARAOGLU, SENGUL (Asian Journal of Chemistry, 2010)
The present study was conducted to evaluate chemical compositions and antimicrobial and antioxidant activities of essential oils from trunk barks of Eucalyptus globulus, Juniperus oxycedrus L, Pinus nigra, Cedrus libani A. Rich, Abies equi-trojani, Cupressus sempervirens, Juglans regia and Alnus glutinosa Mill. The chemical composition of hydro-distilled essential oils of the 8 trunk-bark samples was analyzed by gas chromatography-mass spectrometry. E. globulus, J. oxycedrus, P. nigra, C. libani, A. equi-trojani, C. sempervirens, J. regia and A. glutinosa 56, 52, 34, 56, 57, 46, 13 and 14 components were identified in the essential oils of the plants mentioned above, respectively. Antioxidant activities were measured employing free radical, 2,2-diphenyl- 1-picrylhydrazyl (DPPH) scavenging ability of the samples. All essential oils tested showed moderate free radical scavenging activity. The essential oil of C. sempervirens showed the highest scavenging activity (SC50: 70 μg mL-1) while that of A. equi-trojani showed the lowest (SC50: 5480 μg mL-1). The antimicrobial activity was studied by the agar diffusion method using 5 bacteria and a yeast-like fungus. The essential oils of the 8 species extended significant activity against C. tropicalis. The essential oil of C. libani was particularly active against the 5 bacteria studied with an minimal inhibitory concentration (MIC) at 250 μg mL-1 inactive.